Analysis of erythroid nuclear proteins binding to the promoter and enhancer elements of the chicken histone H5 gene. - Sun, J M (1992)
The chicken erythroid proteins binding to the histone H5 5' promoter and 3' erythroid-specific enhancer regions were identified. In DNase I footprinting and gel mobility shift experiments with immature adult erythrocyte nuclear extracts, we have demonstrated the binding of proteins to the GC-box, a high affinity Sp1 binding site, and to the upstream promoter element. We have previously demonstrated that a multisubunit complex containing the transcription factor GATA-1 was associated with the enhancer. Here, we show that the enhancer region also has four Sp1 binding sites (one medium and three weak affinity, one of which may also bind the CACCC factor), a potential NF-E4 binding site, and a binding site for a NF1-like factor. The results of gel mobility-shift and competition experiments provide evidence that the Sp1 binding sites are associated with a high molecular mass (greater than 450 kDa), Sp1 containing protein complex. We propose that Sp1 multimers bound at the promoter and enhancer interact to mediate the juxta-positioning of the enhancer and promoter elements, bringing the GATA-1 multisubunit complex next to the initiation site. The GATA-1 complex may contribute to the protein-protein interactions between the enhancer and promoter.